Question

 

 

Solution

Correct option is

32

Hence f2(x) + g2(x) is constant. Thus f2(16) + g2(16)= f2(2) + g2(2) = f2(2) + (f’(2))2 = 16 + 16 = 32.

SIMILAR QUESTIONS

Q1

Let f(x + y) = f(xf(y) for all xy Ïµ R and suppose that is differentiable at 0 and f’(0) = 4. If f(x0) = 8 then f’(x0) is equal to

Q2

A function f (x) is defined for x > 0 and satisfies f(x2) = x3 for all x > 0. Then the value of f’(4) is

Q3

Let P(x) be a polynomial of degree 4, with (2) = –1, P’ (2) = 0, P’’ (2), P’’’ (2) = –12 and Piv(2) = 24. The value of P’’(1) is

Q4

Give a function g which has derivative g’(x) for all x satisfying g’(0) = 2 and g(x + y) = ey g(x) + ex g(y) for all xy Ïµ R, g(5) = 32. The value ofg’(5) – 2e5 is